Resonant cavity perturbation: a promising new method for the assessment of total body water in children. (4th November 2015) - Oldroyd, Brian; Robinson, Martin; Lindley, Elizabeth; Rhodes, Laura; Hind, Karen
Abstract: The accurate measurement of total body water (TBW) in children has important clinical and nutritional applications. Resonant cavity perturbation (RCP) is a new method for estimating TBW. This method measures the dielectric properties of the body which are related to body water. For RCP measurements, each subject lay supine on a bed inside a screened room which acts as a resonant cavity. A network analyser measures the frequencies of two low-order cavity resonances of the room, with electric-field vectors that were respectively vertical and horizontal, the resonant frequency shifts relative to the empty room are then derived. These frequency shifts correlates with TBW. The aims of this present study were to (a) develop TBWRCP predictive equations for children using TBWdil as the criterion method, (b) cross-validate the derived equations, (c) determine precision of the TBWRCP method, and (d) compare the criterion method TBWdil with three methods of estimating TBW: RCP, MFBIS and anthropometry. Predictive equations, independent of sex, were developed with linear regression in a group of 36 children. The relationship between combined RCP frequency shifts and TBWdilution had an r 2   =  0.90 and standard error of the estimate (SEE)  =1.42 kg. Multiple regression analysis, that included a term for body mass index, only had a small effect on r 2   =  0.93 and SEE  =  1.25 kg. In vivo TBW precision for the vertical, horizontal and combined frequency modes ranged from 0.7 to 3.4%. Bland–Altman analysis indicated close agreement between the criterion method TBWdil and the three other methods of TBW estimation. Mean differences were TBWRCP(2)   =  0.01  ±  /−  1.34 kg, TBWMFBIS   =  0.45  ±  /−  1.35 kg, TBWAnthropometry   =  0.29  ±  /−  1.29 kg. Currently the RCP method does not significantly improve the prediction of TBW compared to MFBIS and anthropometry in this initial study. However the derived equation was independent of sex and body size had only a small effect.